Adsorption Studies of Cu(II) onto Total Polysaccharide Extracted from Astragals - Li, Shulan; Gu, Xuan; Hu, Yuzhu (Asian Journal of Chemistry, 2012)
The adsorption studies of Cu(II) onto total polysaccharide extracted from astragals were carried out at different temperatures. The adsorption data could be fitted by Langmuir isotherm and Freundlich isotherm. It was noted that increase of temperature would result in a higher Cu(II) loading per unit weight of total polysaccharide. The thermodynamic parameters such as DH, DG and DS were also determined.